Power transmission lines electromagnetic pollution with consideration of soil resistivity - Ali Elgayar; Zulkurnain Abdul-Malek; Ruqayyah Othman; Ibtihal Fawzi Elshami; A. M. Elbreki; Visa Musa Ibrahim; Mohammed Imran Mousa; Chin-Leong Wooi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
The alternating current (AC) total interference of power lines may pose a threat to personnel and equipment in its vicinity. The main objective of this work is to determine the electromagnetic distribution and induced voltages on human body, equipment, and houses due to the AC total interference for different soil resistivities. The electromagnetic field and induced voltages may cause health problems to the human body and put it at risk. Two main approaches were used to compute the electromagnetic and induced voltages, namely the field approach, which is based on electromagnetic field distribution, and the circuit approach, which uses the circuit grounding analysis to compute the conductive interference and then uses the circuit based models to compute the inductive interference. Human body, steel houses and 10-km-long transmission line were modelled. The soil resistivity was varied, and the induced voltages obtained from both approaches were compared. Soil resistivity and soil structure are important parameters that affect the AC interference level. The results show that the touch voltage increases when the distance between electromagnetic source and human body increases. For high soil resistivity, the danger of the touch voltage becomes more prominent compared to that for low soil resistivity. Power system voltage level and soil resistivity are two key factors influencing the induced voltage level.